Measuring Maintainability of Object Oriented Design: A Revisit (International Journal of Innovative Research in Computer Science & Technology, 2020)
Maintainability has always been an elusive  concept. Software maintainability is an external software  quality attributes that estimate the complexity and effort  required for maintaining software. The key concern of this  review paper will be organized study on maintainability considering in view by its sub factors and metrics  implementation of software maintainability keeping in  mind to supports the maintenance process and facilitates  the formation of improved quality software. In this paper  studies accomplish a systematic literature review to have  widespread facts of maintainability research and its feature  factors and related measurements. Finally study does a  comparative analysis on software maintainability models  developed by various researchers/area experts including  their contribution and limitation. In last our effort is to find  the known wide-ranging and complete model or framework  for quantifying the maintainability of object oriented  software at an initial stage of development life cycle.
Keywords: Modularity; Reusability; Analyzability; Modifiability; Testability; Maintainability; Maintainability Measurement; Object Oriented Design; Software Quality